Inventarisation and identification of fish in the Tangun River, Pekanbaru, Riau Province - Laylatul Usna; Deni Efizon; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Tangun River is one of the Kampar Kanan River tributaries. During the rainy season, however, the water level of the Kampar River increase, flow to the Tangun River and enable fish to enter that river. As the information of fish present in that fish is rare, a study aims to inventarize and identify fish that inhabit that river was conducted in Februari-April 2016. Samplings were conducted weekly and the captured fishes were then identified based on Kottelat et al (1993) dan (2013). There were 707 fish sampled and they were belonged to 17 species (6 Ordos, 13 Families). The common fish in the river were Esomus metallicus, Pterygoplichthys pardalis, Poecilia reticula, and Trichogaster trichopterus, while the rare fishes were Trichopsis vittata, Ompok hypophthalmus and Helostoma temminckii.Keyword: Inventarisation , identification, Tangun River, Pekanbaru, Riau